2009
DOI: 10.1080/00365510902802278
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aldosterone blockade on left ventricular function and clinical status during acute myocardial infarction

Abstract: In concordance with these findings, the ejection fraction was slightly higher in Group A than in Group B, although this was not statistically significant (47% versus 44%). This trend continued during a 6-month follow-up after randomization. Our findings suggest that early administration of aldosterone blockers provides additional benefits after AMI, reducing the incidence of post-MI angina pectoris and rhythm and conduction disturbances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…All trials were placebo controlled except three trials [ 22 ][ 23 ][ 24 ] which applied routine treatment. Nine trials [ 25 ][ 26 ][ 27 ][ 28 ][ 13 ][ 29 ][ 30 ][ 31 ][ 24 ] assessed the effect of AAs in post-AMI patients with left ventricular dysfunction; while the other trials recruited HF patients. Duration of follow-up varied from 3 to 44 months.…”
Section: Resultsmentioning
confidence: 99%
“…All trials were placebo controlled except three trials [ 22 ][ 23 ][ 24 ] which applied routine treatment. Nine trials [ 25 ][ 26 ][ 27 ][ 28 ][ 13 ][ 29 ][ 30 ][ 31 ][ 24 ] assessed the effect of AAs in post-AMI patients with left ventricular dysfunction; while the other trials recruited HF patients. Duration of follow-up varied from 3 to 44 months.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, reproducibility of the results in patients taking optimal medical therapy with antiremodeling effects was unclear. Uzunhasan et al [21] have reported that LV EF and volumes did not change in AMI patients who were using optimal medical therapy including angiotensin converting enzyme inhibitors and b blockers compared with additional spironolactone therapy during the 6-month follow-up. Weir et al [19] have found only the modest beneficial effect of eplerenone on LV remodeling in a cohort of patients with LV systolic dysfunction early after AMI.…”
Section: Discussionmentioning
confidence: 99%
“…Nine RCTs [ 11 , 12 , 18 22 , 25 , 28 ] involving 10,702 post-AMI patients showed a significant 14% reduction (10.61% in the MRA groups vs. 12.04% in the control groups) in new or worsening heart failure (HF) after MRA treatment ( Figure 6 ). Excluding the EPHESUS trial [ 11 ] with a weight of 79.9%, RR resulted in no statistical significance: from (0.86, 95% CI (0.77, 0.95), P =0.004, I 2 = 0%) to (0.83, 95% CI (0.65, 1.05), P =0.12, I 2 = 0%).…”
Section: Resultsmentioning
confidence: 99%
“…Data were pooled using a fixed effects model, when I 2 values were below 50%; otherwise, a random effects model was used. If similar estimates were obtained by both [18] Randomized, placebo Yes 12 5 Italy Pitt (2003) [11] Randomized, double-blind, placebo Yes 16 7 Multiple Hayashi (2003) [19] Randomized, nonplacebo No 1 6 Japan Di Pasquale (2001) [20] Randomized, double-blind, placebo No 6 5 Italy Di Pasquale (2005) [21] Randomized, double-blind, placebo No 6 5 Italy Uzunhasan (2009) [22] Randomized, double-blind, placebo Yes 6 7 Turkey Kayrak (2010) [23] Randomized, nonplacebo No 6 5 Turkey Weir (2011) [24] Randomized, double-blind, placebo No 5.5 7 UK Kampourides (2012) [25] Randomized, open-labeled, nonplacebo No 24 6 Greece Wu (2013) [26] Randomized, placebo No 12 6 China Vatankulu (2013) [27] Randomized, nonplacebo Yes 6 5 Turkey Montalescot (2014) [28] Randomized, double-blind, placebo Yes 10.5 7 Multiple Beygui (2016) [12] Randomized, open-labeled, blinded endpoint, nonplacebo Yes 6 5 Multiple Bulluck (2019) [13] Randomized, double-blinded, placebo Yes 3 7 UK ITTA: intention to treat analysis. 3 Cardiovascular Therapeutics methods, we only reported the random effects results to cover possible heterogeneity, because three drugs and different patients were included particularly in control groups.…”
Section: Statistical Analysis Meta-analysis Was Performed Bymentioning
confidence: 87%
See 1 more Smart Citation